Philippine medical thesaurus on anatomy musculoskeletal system and persons in Pangasinan - Capito, Jertrude B.; Quiros, Edgardo B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study, a pioneer work in the making of the Philippine medical thesaurus in Pangasinan was undertaken primarily to collect, translate, and organize medical Pangasinan terms in the musculoskeletal system and persons in aid to the development of the first Medical thesaurus in Pangasinan language. At the start, the researcher had encountered a lot of obstacles and resistance from the Pangasinenses. The needed assistance for the project was met with negative reactions. The medical terms were highly technical and the unfamiliarity of the terms to them resulted in their reluctance to help which also the influence of the English language, intermixed with the native language and become the way of communication in all communities was a deterrent for the fast and easy collection of translated terms. To begin the research, the appropriate methodologies used in the research were carefully studied and weighted in terms of facility and usefulness. The initial step was downloading of the medical terms of the musculoskeletal system and the persons from the MeSH. The target was to translate these medical terms into Pangasinan terms. The ranked Pangasinan dictionaries were consulted first for any possible translations. If dictionaries could not provide enough translations, the researcher had gone to Pangasinan to look for native speakers. Prepared worksheets containing medical terms were provided to the respondents to give any translation of the given terms. A tape recorder and a diagram for the anatomy of the musculoskeletal system was used by the researcher as an instruments during the interviews.
Respondents were located through referrals. All of them were native of Pangasinan, who were born and grew up in towns where Pangasinan was the common language. Two were orthopedic doctors who had been in practicing their profession for several years. The other two were writers, a veterinarian and a teacher. They were also qualified having been familiar with some of the terms. The researcher finally collected 61 translated for the musculoskeletal system and 74 for persons. The numbers of collected terms were adequate enough to meet the target of this study.
The Pangasinan medical thesaurus was work of sheer patience and diligence. However, the study was both amazing and educational. It embodied linguistic approaches like the use of guidelines and policies in the construction of a thesaurus. While done in a limited of time, a tool like this could be developed for the organizing of the medical information in Pangasinan language. The result of this study would be a vital for the further development and construction of this thesaurus. These are the suggested recommendation by the researcher. whenever there are terms with no available translations, the Philippine language experts should be consulted. Pangasinan doctors should be encouraged to use the Pangasinan language in their medical practice. There should be a great concern among the people to preserve this one legacy by focusing on the importance of this language.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings -- Medicine -- Philippines -- Pangasinan; Musculoskeletal system -- Anatomy; Pangasinan language -- Medical Pangasinan